2012
DOI: 10.1155/2012/934968
|View full text |Cite
|
Sign up to set email alerts
|

Right-Sided Pyriform Sinus Fistula: A Case Report and Review of the Literature

Abstract: Objectives. Pyriform sinus fistulae arise from disturbances in the development of the fetal third and fourth branchial pouches and are predominantly found on the left side. We report the rare case of a right-sided pyriform sinus fistula presenting as a lateral neck abscess. Study Design. Case report. Methods. A 24-year-old woman presented with a two-week history of right-sided neck abscess. A fluoroscopic sinogram revealed a fistulous tract extending from the abscess to the apex of the right pyriform sinus. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 13 publications
3
27
0
2
Order By: Relevance
“…Further, CT-fistulography could provide more detailed information about the lesion and it is helpful in surgical planning [33]. In addition, the internal opening of branchial anomalies may be demonstrated with esophagography, although this procedure is difficult during inflammation: in these cases, a direct laryngoscopy could be performed [10,31,34,38]. Even our patient with piriform sinus fistula underwent fistulography to define the course of the lesion.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Further, CT-fistulography could provide more detailed information about the lesion and it is helpful in surgical planning [33]. In addition, the internal opening of branchial anomalies may be demonstrated with esophagography, although this procedure is difficult during inflammation: in these cases, a direct laryngoscopy could be performed [10,31,34,38]. Even our patient with piriform sinus fistula underwent fistulography to define the course of the lesion.…”
Section: Discussionmentioning
confidence: 96%
“…Nicoucar et al [10] reported that piriform sinus anomalies presented primarily on the left side (89 %), usually as neck abscess (39 %) or acute suppurative thyroiditis (33 %); other reported presentations are: upper respiratory infections, recurrent retropharyngeal abscess and cellulitis, odynophagia, stridor and mediastinitis [31]. Interestingly, Shino et al [32] reported a case of pyriform sinus fistula infection with double tract.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The left‐sided preponderance of these anomalies is thought to be attributable to the asymmetric development of the fourth arch vascular structures and the involution of the ultimo branchial body on the right side. Approximately 93–97% of fourth pouch anomalies are left‐sided, although right‐sided anomalies are sporadically reported and women are slightly more prone …”
Section: Discussionmentioning
confidence: 99%
“…L a s f í s t u l a s d e l s e n o p i r i f o r m e ( F S P ) son anomalías poco frecuentes de los arcos branquiales, producto de la obliteración incompleta de la tercera o cuarta bolsa faríngea durante la séptima semana de gestación. 1,2 Una teoría más reciente del origen de la malformación plantea que deriva del conducto timofaríngeo. 2 Más del 95 % se localizan en el lado izquierdo y se extienden desde el ápex del seno piriforme de la hipofaringe hasta la glándula tiroides o el espacio peritiroideo.…”
Section: Introductionunclassified